The Influence of the Number Block Abacus on the Early Arithmetic Ability of 5 to 6 Year Old Children - Saputri, Cindah Ayu; Ilhami, Akmillah (Universitas Pahlawan Tuanku Tambusai, 2025)
Early childhood education is very important for the physical and mental development of children from birth to the age of six, when they experience rapid growth known as the